Relevance of flexibility versus radial force in rigid versus more flexible venous stents?. (August 2019) - van Vuuren, Timme MAJ; de Wolf, Mark AF; Wittens, Cees HA
Introduction: Deep venous stenting has gained increasing interest. More flexible venous stents are thought to gain superior clinical outcomes. This research evaluated the patency and clinical outcomes between more rigid stents and more flexible stents. Material and methods: The Venous Clinical Severity Score, Villalta, complication rates and patency rates were evaluated. The more rigid stents included the Sinus XL, the Veniti VICI and the Sinus Obliquus. The flexible group included the Zilver Vena or the Sinus Venous stents. Results: Differences in Venous Clinical Severity Score (p = 0.09) and Villalta score were found (p = 0.28). Tapering (0 versus 5, p = 0.03) and bad alignment were found (0 versus 5, p = 0.03). The rigid stents showed patency rates of 80, 86 and 92% compared to 88, 96 and 98% in the flexible group. Conclusion: Dedicated venous stents show good patency outcomes and clinical results. Tapering and bad alignment between connecting stents are more frequently seen in more rigid stents.